2017
DOI: 10.1016/j.bpj.2017.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Leaf Trichomes as Acoustic Antennae

Abstract: The much studied plant Arabidopsis thaliana has been reported recently to react to the sounds of caterpillars of Pieris rapae chewing on its leaves by promoting synthesis of toxins that can deter herbivory. Identifying participating receptor cells-potential "ears"-of Arabidopsis is critical to understanding and harnessing this response. Motivated in part by other recent observations that Arabidopsis trichomes (hair cells) respond to mechanical stimuli such as pressing or brushing by initiating potential signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Zhou et al (2016) proposed that trichomes behave as an active mechanosensor, converting physical signals such as mechanical touch from insects into chemical signals like calcium oscillation and pH shift of skirt cells to elicit various defensive reactions. The mechanic stimuli could also be combined with vibrational stimulation of A. thaliana trichomes associated with feeding caterpillars (Liu et al 2017b).…”
Section: Other Functions Not Related To the Occurrence Of Phenolic Compounds In Trichomesmentioning
confidence: 99%
“…Zhou et al (2016) proposed that trichomes behave as an active mechanosensor, converting physical signals such as mechanical touch from insects into chemical signals like calcium oscillation and pH shift of skirt cells to elicit various defensive reactions. The mechanic stimuli could also be combined with vibrational stimulation of A. thaliana trichomes associated with feeding caterpillars (Liu et al 2017b).…”
Section: Other Functions Not Related To the Occurrence Of Phenolic Compounds In Trichomesmentioning
confidence: 99%
“…For instance, trichome geometry, orientation, and position could play a role in keeping predators at bay ( Salerno et al., 2018 ; Vermeij, 2015 ). An elegant modeling study recently showed that mechanosensitive trichomes that produce defensive compounds in response to vibrations specifically respond to acoustic waves produced by chewing caterpillars ( Liu et al., 2017 ). Interestingly, those trichomes tend to accumulate near leaf veins.…”
Section: Structural Patterns: Diversity Overview and Biological Functionsmentioning
confidence: 99%
“…These structures were shown to act as acoustic antennae of plants responding to vibrations associated with the feeding of caterpillars. 45,46 Recent studies have confirmed that leaf trichomes do indeed recognize the caterpillar feeding vibrations which provide relevant cues for allowing plant recognition of herbivores. 47 Pickard summarized all her findings in 2011 in a new model of phyllotaxis involving waves of auxin fluxes and mechanosensory signaling in 2011.…”
Section: Textmentioning
confidence: 98%